High Affinity Binding Sites for Activated Protein C and Protein C on Cultured Human Umbilical Vein Endothelial Cells - Bangalore, Neelesh; Drohan, William N; Orthner, Carolyn L (Thrombosis and Haemostasis, 1994)
Activated protein C (APC) is an antithrombotic serine proteinase having anticoagulant, profibrinolytic and anti-inflammatory activities. Despite its potential clinical utility, relatively little is known about its clearance mechanisms. In the present study we have characterized the interaction of APC and its active site blocked forms with human umbilical vein endothelial cells (HUVEC). At 4° C 125I-APC bound to HUVEC in a specific, time dependent, saturable and reversible manner. Scatchard analysis of the binding isotherm demonstrated a Kd value of 6.8 nM and total number of binding sites per cell of 359,000. Similar binding isotherms were obtained using radiolabeled protein C (PC) zymogen as well as D-phe-pro-arg-chloromethylketone (PPACK) inhibited APC indicating that a functional active site was not required. Competition studies showed that the binding of APC, PPACK-APC and PC were mutually exclusive suggesting that they bound to the same site(s). Proteolytic removal of the N-terminal γ-carboxyglutamic acid (gla) domain of PC abolished its ability to compete indicating that the gla-domain was essential for cell binding. Surprisingly, APC binding to these cells appeared to be independent of protein S, a cofactor of APC generally thought to be required for its high affinity binding to cell surfaces. The identity of the cell binding site(s), for the most part, appeared to be distinct from other known APC ligands which are associated with cell membranes or extracellular matrix including phospholipid, thrombomodulin, factor V, plasminogen activator inhibitor type 1 (PAI-1) and heparin. Pretreatment of HUVEC with antifactor VIII antibody caused partial inhibition of 125I-APC binding indicating that factor VIII or a homolog accounted for ∼30% of APC binding. Studies of the properties of surface bound 125I-APC or 125I-PC and their fate at 4°C compared to 37 °C were consistent with association of ∼25% of the initially bound radioligand with an endocytic receptor. However, most of the radioligand appeared not to be bound to an endocytic receptor and dissociated rapidly at 37° C in an intact and functional state. These data indicate the presence of specific, high affinity binding sites for APC and PC on the surface of HUVEC. While a minor proportion of binding sites may be involved in endocytosis, the identity and function of the major proportion is presently unknown. It is speculated that this putative receptor may be a further mechanisms of localizing the PC antithrombotic system to the vascular endothelium.